APPLICATION OF KVISOFT MAKER-BASED FLIPBOOK PROBLEM BASED LEARNING (PBL) MODEL BASED ON KINEMASTER TO IMPROVE CAPABILITIES HOTS LITERACY FOR GRADE XI STUDENTS OF SMA NEGERI 1 PERCUT SEI MASTER MATTER REACTION RATE - Pasaribu, Putri Cantika; Suyanti, Retno Dwi (Jurnal Pendidikan dan Pembelajaran Kimia, 2024)
There several problems in efforts to improve students' literacy host skills caused by the inaccuracy of learning models and media used for abstract chemical material, so it is necessary to use appropriate learning models and media. This study aims to determine the significant differences between students host literacy skills after using the problem based learning (PBL) model with kinemaster flipbook media and to find out which aspects of mastery develop throught the problem based learning PBL model with kinemaster based media. Research design using one group pretest posttest sample selection is done by random sampling technique. The sample stuied was high svhool students in class 12 Sains 4 as many as 32 students. The instruments used were multiple choice test and interviews. The relust this study showed that there were 26 valid question with a reliability 0,734. The normality test found that the data were normally distributed. Data analysis showed that the N-Gain value met the high criteria, namely 0,7186 (71,86%). Hypothesis testing obtained tvalue = 2,232 with ttabel = 1,697 thus t count > than t table so that the research hypothesis is accepted. This means that there a significant difference between the ability of students to host literacy after using the problem based learning (PBL) model with kvisoft flipbook media kinemaster based maker. The host literacy of student literacy that developed the most in this study through the problem based learning (PBL) model with kvisoft maker based flipbook media was C4 reasoning with a presentation of 71,96%.Keywords: Media Flipbook Kvisoft Maker, Kinemaster, PBL, HOTs LiteracyDOI: 10.23960/jppk.v13.i1.2024.13